Tailoring Food Biopolymers into Biogels for Regenerative Wound Healing and Versatile Skin Bioelectronics - Zeng, Qiankun; Peng, Qiwen; Wang, Fangbing; Shi, Guoyue; Haick, Hossam; Zhang, Min (Nano-Micro Letters, 2023)
An increasing utilization of wound-related therapeutic materials and skin bioelectronics urges the development of multifunctional biogels for personal therapy and health management. Nevertheless, conventional dressings and skin bioelectronics with single function, mechanical mismatches, and impracticality severely limit their widespread applications in clinical. Herein, we explore a gelling mechanism, fabrication method, and functionalization for broadly applicable food biopolymers-based biogels that unite the challenging needs of elastic yet injectable wound dressing and skin bioelectronics in a single system. We combine our biogels with functional nanomaterials, such as cuttlefish ink nanoparticles and silver nanowires, to endow the biogels with reactive oxygen species scavenging capacity and electrical conductivity, and finally realized the improvement in diabetic wound microenvironment and the monitoring of electrophysiological signals on skin. This line of research work sheds light on preparing food biopolymers-based biogels with multifunctional integration of wound treatment and smart medical treatment. Highlights: 1 This food biopolymer-based biogel unites the challenging needs of elastic yet injectable wound dressing and skin bioelectronics in a single platform. 2 This is the first demonstration of a hydrogel dressing that satisfies both deep and superficial wounds, and for the accelerated healing of diabetic wounds. 3 Biogel-based flexible skin bioelectronic can serve as a “fever indicator” and monitoring human activities and tiny electrophysiological signals, providing important clinical information for the rehabilitation training of the wounded.